Euro Area Policies : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2018)
Overall the resilience of large euro area banks has improved, but important vulnerabilities remain. Capital buffers are in aggregate sizeable relative to immediate threats, but some banks are especially vulnerable to credit risk and others to market risks, including a substantial rise in risk premia. The banking system as a whole has ample liquidity, against a backdrop of ECB support. At a structural level, low profitability is found in many banks across all business models, despite improving conjunctural conditions. The interconnectedness analysis shows that strong buffers are effective in dampening both vulnerabilities and onward transmission. Risks to financial stability relate mainly to tighter financial conditions, weaker growth, and policy and geopolitical uncertainties. The withdrawal of the United Kingdom from the EU (Brexit) could potentially disrupt financial market and services, and thus the wider economy. Also, policy reversals could hurt debt sustainability and test the cohesion of policy making in the union.